Magnetic resonance imaging (MRI) Raw Data Results and Its Diagnosis of Spinal Cord Injuries: Patient Case - Sehrish Rana Rajpoot; Muhammad Wasim Tasleem; Muhammad Danish; Hafiz Muhammad Ayub; Tasleem Kanwal; Mehboob Ahmad; Aalia Nazir; Muhammad Ismail; Muhammad Salman (Universitas Pendidikan Indonesia (UPI), 2021)
In the present study, we discussed the best techniques for the clear scan of the spine. For this investigation, it was found that magnetic resonance imaging (MRI) is a better technique as compared to others. It gives proper images and results in the case of hard tissues like the spine compared to X-Ray and computed tomography (CT) scans. It is also better in sense of it has a small radiation risk as compared to X-Ray and CT have some radiation hazards to patient health. Thirteen patients were scanned by MRI technique and the result was evaluated. It is a non-invasive technique and is used for different pathological diseases. It was found that most doctors and surgeons preferred the MRI techniques in the case of the Spinal Cord. Many radiologists exercised X-rays, CT, and MRI methods for viewing clear images of the spine. It was concluded that MRI is the best technique than X-rays and CT scans. MRI is a modality choice for the evaluation of soft tissue changes in the case of Cord. In the case of the Spinal Cord MRI better evaluates changes in spinal cord compression due to its high-resolution property. The CT could not tell us about the soft tissue change in Cord however it more clearly tells us about the fracture of vertebral bodies and posterior elements.